Feasibility study on improving of 5-seater helicopter forward flight speed [compact disc] - 404297 Nik Ahmad Ridhwan Nik Mohd. (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006